Intangible Heritage and Tourism: Contemporary Discussions Between Brazil and Mexico - Christofoletti, Rodrigo (Anais Brasileiros de Estudos Turísticos, 2022)
The Intangible Cultural Heritage of Humanity, in accordance with the Convention for the Safeguarding of the Intangible Cultural Heritage, adopted by UNESCO in 2003, includes the practices, representations, expressions, knowledge and techniques, together with the instruments, objects and cultural places that it they are associates, which communities, groups and, in some cases, individuals recognize as an integral part of their Cultural Heritage. One of the most visible vectors in the dissemination and protection of these cultural manifestations is tourism, which each year promotes new spaces to recognize their respective material heritage, but which, since the beginning of the century, has also directed its attention to expanding the practices. intangible heritage. In this text, we will make a brief comparison between the seventeen intangible heritage registered in the two most representative Latin American countries in terms of tourist visibility (Brazil and Mexico) and we will present how these countries have worked in the search for a broader understanding. of the bonuses and charges of the UNESCO seal, understanding the relationship between tourism and intangible heritage as a relevant soft power.